(untitled) (Indonesian Minority Justice Review, 2024)
This paper examines the legal and political dynamics that contribute to the systemic discrimination against Indonesia’s indigenous peoples. Despite constitutional guarantees of equality, indigenous communities in Indonesia face significant challenges in securing their rights to land, culture, and political representation. The research focuses on the impact of national development policies, land tenure laws, and environmental regulations on indigenous peoples, particularly in relation to land conflicts with state and corporate interests. By analyzing legal cases, government policies, and interviews with indigenous leaders and legal experts, the study highlights the ways in which legal frameworks often marginalize indigenous communities, prioritizing economic development over cultural preservation and land rights. The paper argues that Indonesia’s legal system, while formally committed to protecting indigenous rights, is often complicit in practices that perpetuate exclusion. It concludes with a call for comprehensive legal reform, including the recognition of indigenous peoples’ customary law and greater political representation, to address these structural inequities.